2015
DOI: 10.1080/00223131.2015.1078262
|View full text |Cite
|
Sign up to set email alerts
|

Development ofLOcal-scaleHigh-resolution atmosphericDIspersionModel usingLarge-EddySimulation. Part 5: detailed simulation of turbulent flows and plume dispersion in an actual urban area under real meteorological conditions

Abstract: We have developed a LOcal-scale High-resolution atmospheric DIspersion Model using Large-Eddy Simulation (LOHDIM-LES) to assess the safety at nuclear facilities and to respond to emergency situations resulting from accidental or deliberate releases of radioactive materials (e.g., a terrorist attack in an urban area). In parts 1-4, LESs of turbulent flows and plume dispersion over a flat terrain, around an isolated building, within building arrays with different obstacle densities, and within an actual urban ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The grid spacing is 20 m in the horizontal directions and 2.5-64 m stretched in the vertical direction based on an orthogonal grid system. In the previous study, we conducted LESs of urban boundary layer flows in the urban central district by coupling with a MM model and showed reasonable results in comparison to the field experimental data of vertical profiles of wind speeds and directions (Nakayama et al, 2015). Those calculation conditions such grid resolution and computational domain were almost the same as the present ones.…”
Section: Les Computational Conditionsmentioning
confidence: 74%
See 2 more Smart Citations
“…The grid spacing is 20 m in the horizontal directions and 2.5-64 m stretched in the vertical direction based on an orthogonal grid system. In the previous study, we conducted LESs of urban boundary layer flows in the urban central district by coupling with a MM model and showed reasonable results in comparison to the field experimental data of vertical profiles of wind speeds and directions (Nakayama et al, 2015). Those calculation conditions such grid resolution and computational domain were almost the same as the present ones.…”
Section: Les Computational Conditionsmentioning
confidence: 74%
“…Therefore, first, we proposed the treatment of the inflow boundary conditions in order to automatically input wind velocity data obtained by the MM model into the LES model under neutral stability conditions, depending on mean wind directions in the meteorological field (Nakayama et al, 2012(Nakayama et al, , 2015. Figure 1 shows a schematic diagram of the treatment of inflow boundary conditions in the LES model.…”
Section: Generation Of Turbulent Inflows From MM Outputsmentioning
confidence: 99%
See 1 more Smart Citation
“…One-way coupled obstacle-resolving LES has been applied to a built environment by Nakayama et al (2016) and by Vonlanthen et al (2016Vonlanthen et al ( , 2017. Also the present PALM implementation has already been demonstrated by MAronga et al (2019); Maronga et al (2020) and applied to obstacle-resolving urban studies (Kurppa et al, 2019;Auvinen et al, 2020a;Karttunen et al, 2020;Kurppa et al, 2020) using the one-way coupling.…”
mentioning
confidence: 76%
“…This implies that it is difficult to ensure the representativeness of the observations at a stationary point to be assimilated into turbulent flows and plume dispersion in the complex urban environments. Nakayama et al (2016) conducted LESs of plume dispersion in the urban central district of Oklahoma City under realistic atmospheric conditions during the field campaign Joint Urban 2003 by coupling the LES model with a mesoscale meteorological simulation (MMS) model and concluded that the prediction accuracy of the high-resolution simulations highly depends on the quality and reproducibility of the wind speed and direction simulated by the mesoscale model against the observed data during the field experiments.…”
Section: Introductionmentioning
confidence: 99%